A comparative analysis of the policy process of elite sport development in China and the UK (in relation to three Olympic sports of artistic gymnastics, swimming and cycling) - Zheng, J. (Loughborough University, 2015)
This thesis seeks to analyse the policy making and policy implementation processes of elite sport in China and the UK, covering the period 1992-2012. Three sports are selected for detailed cases studies: artistic gymnastics, swimming and cycling. They represent a wide range of sports in two countries, based on their varying competiveness, weights and traditions. Key areas including organisational structure, financial support, talent identification and athlete development, coaching, training, competition opportunities, scientific research and others (including international influence and other sport- and country-specific areas) are identified to organise the discussion. The aim is not only to present key characteristics of the development of each sport in China and the UK respectively and to introduce the successful experience and problems but also to form a basis for the discussion of policy making, policy implementation and policy changes.